Metabolic Changes Following Perinatal Asphyxia: Role of Astrocytes and Their Interaction with Neurons - Logica, Tamara; Riviere, Stephanie; Holubiec, Mariana I.; Castilla, Rocío; Barreto, George E.; Capani, Francisco (Frontiers in Aging Neuroscience, 2016)
Perinatal asphyxia represents an important cause of severe neurological deficits including delayed mental and motor development, epilepsy, major cognitive deficits and blindness. The interaction between neurons, astrocytes and endothelial cells plays a central role coupling energy supply with changes in neuronal activity. Traditionally, experimental research focused on neurons, whereas astrocytes have been more related to the damage mechanisms of perinatal asphyxia. Astrocytes carry out a number of functions that are critical to normal nervous system function, including uptake of neurotransmitters, regulation of pH and ion concentrations, and metabolic support for neurons. In this work, we aim to review metabolic neuron-astrocyte interactions with the purpose of encourage further research in this area in the context of perinatal asphyxia, which is highly complex and its mechanisms and pathways have not been fully elucidated to this day.